Metabolism of T4 Bacteriophage Ghost-Infected Cells II. Do Ghosts Cause a Generalized Permeability Change? - Duckworth, Donna Hardy (1972)
Ghosts appear to alter the barrier function of the cell membrane, allowing the release of phosphorylated sugars which normally cannot pass through the cell membrane, whereas phage do not. No increased influx of normally impermeable compounds is observed in the presence of ghosts, indicating that the loss of membrane function after ghost infection cannot be attributed to a generalized breakdown of the permeability barrier.